Quantifying vertical land motion at tide gauge sites using permanent scatterer interferometric synthetic aperture radar and global navigation satellite system solutions - Rosalie Reyes; Ma. Divina Angela Bauzon; Nikki Alen Pasaje; Rey Mark Alfante; Pocholo Miguel De Lara; Marion Ordillano; Paul Caesar Flores; Abegail Rediang; Patrick Anthony Nota; Fernando Siringan; Ariel Blanco; Dennis Bringas (Spatial Information Research, 2022)

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

Insect herbivory stimulates allelopathic exudation by an invasive plant and the suppression of natives - Giles C. Thelen; Jorge M. Vivanco; Beth Newingham; William Good; Harsh P. Bais; Peter Landres; Anthony Caesar; Ragan M. Callaway (Ecology Letters, 2005)
Exotic invasive plants are often subjected to attack from imported insects as a method of biological control. A fundamental, but rarely explicitly tested, assumption of biological control is that damaged plants are less fit and compete poorly. In contrast, we find that one of the most destructive invasive plants in North America, Centaurea maculosa , exudes far higher amounts of (±)‐catechin, an allelopathic chemical known to have deleterious effects on native plants, when attacked by larvae of two different root boring biocontrol insects and a parasitic fungus. We also demonstrate that C. maculosa plants experimentally attacked by one of these biocontrols exhibit more intense negative effects on natives.